2020
DOI: 10.1371/journal.pntd.0008298
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of co-administered diethylcarbamazine, albendazole and ivermectin during mass drug administration for lymphatic filariasis in Haiti: Results from a two-armed, open-label, cluster-randomized, community study

Abstract: In Haiti, 22 communes still require mass drug administration (MDA) to eliminate lymphatic filariasis (LF) as a public health problem. Several clinical trials have shown that a single oral dose of ivermectin (IVM), diethylcarbamazine (DEC) and albendazole (ALB) (IDA) is more effective than DEC plus ALB (DA) for clearing Wuchereria bancrofti microfilariae (Mf). We performed a cluster-randomized community study to compare the safety and efficacy of IDA and DA in an LF-endemic area in northern Haiti. Ten localitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 25 publications
4
33
3
Order By: Relevance
“…CFA clearance after treatment was somewhat more frequent in those who had lower baseline FTS scores, particularly in children, and this is probably because of their worm loads at baseline. Although CFA clearance rates were higher in the Haiti IDA safety study (20.5-25.5%) than in this study, the Haiti study also found no difference in CFA clearance after IDA or DA [23]. In contrast to our results, clearance of CFA was higher among adults in Haiti.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 99%
See 3 more Smart Citations
“…CFA clearance after treatment was somewhat more frequent in those who had lower baseline FTS scores, particularly in children, and this is probably because of their worm loads at baseline. Although CFA clearance rates were higher in the Haiti IDA safety study (20.5-25.5%) than in this study, the Haiti study also found no difference in CFA clearance after IDA or DA [23]. In contrast to our results, clearance of CFA was higher among adults in Haiti.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 99%
“…Mf clearance rates 12-month post-treatment with either IDA (84%) or DA (62%) were lower in this study than those reported from the parallel study in Haiti (IDA vs DA: 94.4% vs 75.9) [23]. It is possible that this is due to the fact that DEC dosing was based on weight in Haiti and by age in our study.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 74%
See 2 more Smart Citations
“…Similar results were observed in PNG, where a 50% reduction in Og4C3 Ag level was observed at 12 months [ 32 ]. Studies in PNG [ 35 , 36 ] and Haiti [ 37 ] reported that after a single dose of IDA, 95%-97% and 79.5% of Ag-positive participants were still positive after 12 months, respectively. These findings suggest that after treatment with IDA, Ag-positivity is likely to persist for months in the majority of people.…”
Section: Discussionmentioning
confidence: 99%